Sustainability and machinability improvement of Nimonic-90 using indigenously developed green hybrid machining technology. (1st August 2020) - Khanna, Navneet; Agrawal, Chetan; Gupta, Munish Kumar; Song, Qinghua; Singla, Anil Kumar
Abstract: This study compares the turning performance of Nimonic 90 using indigenously developed cryogenic-ultrasonic assisted turning (CUAT) process and cryogenic assisted turning (CAT) process. CUAT process combines the advantages of CAT and ultrasonic-assisted turning (UAT) processes. Both CAT and UAT processes are proven sustainable machining techniques. Experiments are designed using the full factorial method. In this work, machinability is evaluated in terms of energy consumption, carbon emissions, machining characteristics and overall machining cost. It is found that the results using CUAT process are better as compared to the CAT process in terms of decreased energy consumption (up to 20%), carbon emissions and overall machining cost. Further, it is also observed that the surface finish also improved (up to 29%) under the CUAT process as compared to CAT process. These results advocate the sustainable gains of the CUAT process over the CAT process. Graphical abstract: Image 1 Highlights: Cryogenic-ultrasonic assisted turning (CUAT) improves machinability of Nimonic 90. CUAT improves sustainability as compared to cryogenic assisted turning (CAT). Decreased energy consumption (up to 20%) under CUAT as compared to CAT. Decreased carbon emissions and machining cost under CUAT as compared to CAT.